A clinical study on the difference among proteinuria components in preeclampsia and pregnancies complicated with chronic nephrosis. (May 2019) - Zhuang, Xu; Lv, Zhuo-cheng; Shi, Jun; Lin, Jian-hua
Abstract: Objective: To explore proteinuria components in preeclampsia (PE) and pregnancies complicated with chronic nephrosis (PCCN). Methods: A case-control study was conducted with 81 PE and 95 PCCN patients and 192 normal pregnancies from April 2016 to March 2018. The results of a 24 h proteinuria test and a proteinuria component analysis (PCA) of all enrolled patients were collected. Statistical analyses of variance and SNK-q were conducted to identify the difference between PE and PCCN in urinary protein components using SPSS 23.0 software. A Pearson test and linear regression were conducted to explore the association between 24 h proteinuria and PCA. Results: Among the PE, PCCN and control groups, the average values of mAlb(2868.5 ± 3119.3 vs 1586.2 ± 3627.0 vs 21.6 ± 23.6), TRF(252.0 ± 280.5 vs 112.9 ± 164.5 vs 3.1 ± 2.7), α1-MG(40.4 ± 40.7 vs 34.0 ± 38.6 vs 10.3 ± 8.0), β2-MG(1.9 ± 5.1 vs 6.8 ± 15.8 vs 0.9 ± 2.3), and RBP(0.9 ± 1.7 vs 3.1 ± 4.5 vs 0.4 ± 0.7) were significantly different (P＜0.001). According to the SNK-q test, the average value of mAlb and TRF in the PCCN group is lower than that in the PE group, but higher than the control group (P < 0.05). The average value of RBP and β2-MG in the PCCN group was higher than the PE and control groups (P < 0.05). The mAlb, TRF, and α1-MG values separately had a significant correlation with the 24 h proteinuria value in PE. The linear regression equation was 24 h proteinuria value = 0.891*mAlb + 5.969*TRF + 1742.378. The mAlb, TRF, α1-MG, β2-MG, and RBP values separately had a significant correlation with the 24 h proteinuria value in PCCN and a linear regression equation of PCCN was as follows: 24 h proteinuria value = 15.148*TRF + 0.571*mAlb. Conclusions: The proteinuria components of PE and PCCN patients were different in the elevated β2-MG and RBP. The PCA could be a suitable test for qualitative analysis and an antidiastole for PE and PCCN.